177Lutetium SPECT/CT: Evaluation of collimator, photopeak and scatter correction. Issue 9 (13th August 2020) - Huizing, Daphne M. V.; Sinaasappel, Michiel; Dekker, Marien C.; Stokkel, Marcel P. M.; de Wit – van der Veen, Berlinda J.
Abstract: Purpose: The goal of this study was to find the optimal combination of collimator, photopeak and scatter correction for 177 Lutetium ( 177 Lu) SPECT/CT imaging. Methods: Three experiments [sphere‐to‐background ratios (SBR) 50:1, 10:1, and 2:1] were performed with the NEMA Image Quality phantom filled with 177 Lu‐trichloride. SPECT/CT acquisitions were performed with the medium‐energy low‐penetration (MELP) collimator and 99m Tc/Krypton collimator. For each acquisition six reconstructions, all with attenuation correction (AC), were made: the 113‐keV photopeak only, the 208‐keV photopeak only and both photopeaks combined, each with or without scatter correction (SC). Image quality was assessed using contrast‐to‐noise ratios (CNR), quantification accuracy by means of recovery coefficients (RCs) and the spatial resolution using line profiles. Results: With SBR 50:1 and 10:1, both collimators met the Rose criterion (CNR > 5), whereas the MELP collimator showed a higher CNR for the 2:1 ratio. The RCmean was higher with the MELP collimator, most explicit after the 208‐keV AC/SC reconstruction for all acquisitions. The line profiles showed a better spatial resolution for the MELP collimator and the 208‐keV AC/SC reconstructions. Conclusion: 177 Lu SPECT/CT image quality and quantification was most optimal when acquired with the MELP collimator and reconstructed using the 208‐keV photopeak, with AC and SC.